Apparent Diffusion Coefficient in Invasive Ductal Breast Carcinoma: Correlation with Detailed Histologic Features and the Enhancement Ratio on Dynamic Contrast-Enhanced MR Images. (8th August 2010) - Matsubayashi, Roka Namoto; Fujii, Teruhiko; Yasumori, Kotaro; Muranaka, Toru; Momosaki, Seiya
Abstract : Purpose . To investigate the correlation of Apperent Diffusion Coefficient (ADC) values in invasive ductal breast carcinomas with detailed histologic features and enhancement ratios on dynamic contrast-enhanced MRI. Methods and Materials . Dynamic MR images and diffusion-weighted images (DWIs) of invasive ductal breast carcinomas were reviewed in 25 (26 lesions) women. In each patient, DWI, T2WI, T1WI, and dynamic images were obtained. The ADC values of the 26 carcinomas were calculated with b-factors of 0 and 1000 s/mm 2 using echoplanar DWI. Correlations of the ADC values were examined on dynamic MRI with enhancement ratios (early to delayed phase: E/D ratio) and detailed histologic findings for each lesion, including cellular density, the size of cancer nests, and architectural features of the stroma (broad, narrow, and delicate) between cancer nests. Results . The mean ADC was0.915 ± 0.151 × 10 - 3 mm 2 /sec. Cellular density was significantly correlated with ADC values (P = .0184 ) and E/D ratios (P = .0315 ). The ADC values were also significantly correlated to features of the stroma (broad to narrow, P = .0366 ). Conclusion . The findings suggest that DWIs reflect the growth patterns of carcinomas, including cellular density and architectural features of the stroma, and E/D ratios may also be closely correlated to cellular density.